2012
DOI: 10.3758/s13414-012-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

The mental wormhole: Internal attention shifts without regard for distance

Abstract: Attention operates perceptually on items in the environment, and internally on objects in visuospatial working memory. In the present study, we investigated whether spatial and temporal constraints affecting endogenous perceptual attention extend to internal attention. A retro-cue paradigm in which a cue is presented beyond the range of iconic memory and after stimulus encoding was used to manipulate shifts of internal attention. Participants' memories were tested for colored circles (Experiments 1, 2, 3a, 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 95 publications
(253 reference statements)
6
65
0
1
Order By: Relevance
“…For example, neuroimaging studies have found an additional involvement of certain medial and lateral prefrontal areas and stronger activations in parietal regions when the focus of attention is controlled within VWM (Nee & Jonides, 2009;Nobre et al, 2004;Tamber-Rosenau et al, 2011). Moreover, internal attention has also been shown to exhibit distinct behavioral characteristics: Unlike external shifts of attention, internal shifts of attention appear not to be influenced by the initial physical distance of the encoded objects, and beyond a certain threshold time, additional time for internal shifts does not yield additional benefits (Tanoue & Berryhill, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, neuroimaging studies have found an additional involvement of certain medial and lateral prefrontal areas and stronger activations in parietal regions when the focus of attention is controlled within VWM (Nee & Jonides, 2009;Nobre et al, 2004;Tamber-Rosenau et al, 2011). Moreover, internal attention has also been shown to exhibit distinct behavioral characteristics: Unlike external shifts of attention, internal shifts of attention appear not to be influenced by the initial physical distance of the encoded objects, and beyond a certain threshold time, additional time for internal shifts does not yield additional benefits (Tanoue & Berryhill, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the distance between objects at encoding does not affect the time it takes to shift internal attention between the respective representations (Tanoue & Berryhill, 2012).…”
Section: How Many Representations In Vwm Can Be Selected?mentioning
confidence: 99%
“…These effects are not due to modulation of the response to a preferred perceptual stimulus over others (since no perceptual input is present), and no eye movement artifacts (e.g., Matsukura, Luck, & Vecera, 2007) or eccentricity effects (Tanoue & Berryhill, 2012) have been found to explain it.…”
Section: The Retro-cue Effectmentioning
confidence: 95%
“…A few studies have addressed this question by varying the temporal separation between the retro-cue and onset of the test display (hereafter, the cue-test delay). Tanoue and Berryhill (2012) varied the cue-test delay from 100 to 700 ms in a local-recognition task. Significant retro-cue benefits emerged after 300 ms, and they did not increase in size with longer cue-test delays.…”
Section: Time Coursementioning
confidence: 99%
“…Specifically, those studies have shown that directing attention to the location of one previously encoded stimulus using retrocues subsequently enhances the recall of that stimulus (Berryhill, Richmond, Shay & Olson, 2012;Delvenne, Cleeremans, & Laloyaux, 2010;Griffin & Nobre, 2003;Landman, Spekreijse & Lamme, 2003;Lepsien, Griffin, Devlin & Nobre, 2005;Lepsein & Nobre, 2006;Makovski & Jiang, 2007;Makovski, Sussman & Jiang, 2008;Matsukura, Luck & Veraca, 2007;Nobre et al, 2004;Tanoue & Berryhill, 2012;Tanoue, Jones, Peterson & Berryhill, 2013, amongst others). Recent electrophysiological evidence suggests that retro-cues promote the selective access of relevant VSTM representations and bias processing in favour of those representations (Kuo, Stokes & Nobre, 2012).…”
Section: Introductionmentioning
confidence: 99%